Severe Ovarian Hyperstimulation Syndrome in a Woman With Breast Cancer Under Letrozole Triggered With GnRH Agonist: A Case Report and Review of the Literature - Iorio, Giuseppe Gabriele; Rovetto, Marika Ylenia; Conforti, Alessandro; Carbone, Luigi; Vallone, Roberta; Cariati, Federica; Bagnulo, Francesca; Di Girolamo, Raffaella; La Marca, Antonio; Alviggi, Carlo (Frontiers in Reproductive Health, 2021)
We report a rare case of ovarian hyperstimulation syndrome in a 28-year-old woman with breast cancer and PCOS history, despite treatment with letrozole and GnRH agonist triggering in a GnRH antagonist protocol without the administration of any hCG for luteal-phase support. The patient, who underwent controlled ovarian stimulation-oocyte cryopreservation before chemotherapy, required hospitalization. Complete recovery was achieved after treatment with volume expanders, human albumin and cabergoline. On the basis of our case and literature review, it is possible to establish that estradiol modulation with letrozole and GnRH-agonist triggering does not eliminate OHSS risk. Furthermore, it is advisable to postpone GnRH-a depot to minimize the risk of OHSS after the suspension of letrozole, following menstruation or at least 7-8 days after triggering. It would be desirable to identify high risk patients, also on a genetic basis, in order to avoid delays in oncologic treatments which could strongly impact on the life expectancy.